Dynamic Influence Maximization via Network Representation Learning - Sheng, Wei; Song, Wenbo; Li, Dong; Yang, Fei; Zhang, Yatao (Frontiers in Physics, 2022)
Influence maximization is a hot research topic in the social computing field, and has gained tremendous studies motivated by its wild application scenarios. As the structures of social networks change over time, how to seek seed node sets from dynamic networks has attracted some attention. However, all of the existing studies were based on network topology structure data which has the limitations of high dimensionality and low efficiency. Aiming at this drawback, we first convert each node in the network to a low-dimensional vector representation by network representation learning and then solve the problem of dynamic influence maximization in the low-dimensional latent space. Comprehensive experiments on NetHEPT, Twitter, UCI and Wikipedia datasets show that our method can achieve influence diffusion performance similar to state-of-the-art approaches in much less time.